2011
DOI: 10.1111/j.1542-2011.2011.00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dietary Folate Intake on Depressive Symptoms in Young Women of Reproductive Age

Abstract: Multiple logistic regression analysis revealed a reduced incidence of depression in women whose intake of folate exceeded the RDA of 240 μg per day. This finding suggests that dietary folate intake may be causally related to depressive symptoms in women of reproductive age. If results of studies powered to determine causal relationships are similarly positive, folate supplementation could reduce the incidence of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The association between folate status and depression, and the effect of folate administration in the treatment of depression have been addressed by several studies [72,128]. Supplementation of FA [24] or 5-methylfolate [36] may enhance the antidepressant action of certain medications.…”
Section: Protective Effects Of Folate Beyond Ntd Preventionmentioning
confidence: 99%
“…The association between folate status and depression, and the effect of folate administration in the treatment of depression have been addressed by several studies [72,128]. Supplementation of FA [24] or 5-methylfolate [36] may enhance the antidepressant action of certain medications.…”
Section: Protective Effects Of Folate Beyond Ntd Preventionmentioning
confidence: 99%
“…12 Here, we further found a suggestive inverse association between dietary vitamin B6 intake at baseline and depressive symptoms after 3 years. Of seven cross-sectional studies that have examined the association between vitamin B6 intake and depressive symptoms [9][10][11][12][13][14][15] , four have observed an inverse association. [10][11][12]15 Moreover, only two studies have examined the prospective association between vitamin B6 intake and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, a systematic review reported that vitamin B6 had no apparent treatment effect on depression. 8 Although seven crosssectional [9][10][11][12][13][14][15] and two prospective 16,17 studies have examined the association between dietary vitamin B6 intake and depressive symptoms, inconsistent findings were reported. Moreover, only two cross-sectional studies have found an inverse association between depression and plasma concentrations of pyridoxal 5 0 -phosphate (PLP), which is the major and active form of vitamin B6.…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson's disease 76,105 . Supplementation with B-vitamins and folate has enjoyed moderate clinical success in alleviating depressive symptoms 91,92,106 . Recently, S-adenosyl methionine has been touted as a potential treatment for depression, both alone and in conjunction with prescription serotonin reuptake inhibitors (SSRIs) and serotonin-norepinephrine reuptake inhibitors (SNRIs) 94,107 .…”
Section: Introductionmentioning
confidence: 99%
“…. Further studies showed that high plasma homocysteine and low serum folate both increased the risk of depression and increased the duration of depressive episodes, an effect that is especially pronounced in pregnant and postpartum women [90][91][92] .…”
mentioning
confidence: 99%